2022
DOI: 10.3390/ijms232415542
|View full text |Cite
|
Sign up to set email alerts
|

Improved NMDA Receptor Activation by the Secreted Amyloid-Protein Precursor-α in Healthy Aging: A Role for D-Serine?

Abstract: Impaired activation of the N-methyl-D-aspartate subtype of glutamate receptors (NMDAR) by D-serine is linked to cognitive aging. Whether this deregulation may be used to initiate pharmacological strategies has yet to be considered. To this end, we performed electrophysiological extracellular recordings at CA3/CA1 synapses in hippocampal slices from young and aged mice. We show that 0.1 nM of the soluble N-terminal recombinant fragment of the secreted amyloid-protein precursor-α (sAPPα) added in the bath signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…In the aging brain, D-serine levels and NMDAR-mediated synaptic transmission are reduced [33][34][35][36][37][38][39], whereas supplementation with exogenous D-serine in aged rats [34] or mice with low D-serine release due to astrocytic mutations [69] normalize hypofunctional NMDAR responses. Moreover, the beneficial effects of sAPPα, a secreted form of amyloid precursor protein generated by the nonamyloidogenic pathway, on NMDAR-mediated transmission in hippocampal slices of aged mice are partially mediated by the D-serine pathway, as evidenced by an attenuation of these enhancing effects in SR knockout mice [70]. These beneficial effects of D-serine have translated to amelioration of cognitive function in elderly as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the aging brain, D-serine levels and NMDAR-mediated synaptic transmission are reduced [33][34][35][36][37][38][39], whereas supplementation with exogenous D-serine in aged rats [34] or mice with low D-serine release due to astrocytic mutations [69] normalize hypofunctional NMDAR responses. Moreover, the beneficial effects of sAPPα, a secreted form of amyloid precursor protein generated by the nonamyloidogenic pathway, on NMDAR-mediated transmission in hippocampal slices of aged mice are partially mediated by the D-serine pathway, as evidenced by an attenuation of these enhancing effects in SR knockout mice [70]. These beneficial effects of D-serine have translated to amelioration of cognitive function in elderly as well.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that secreted amyloid protein precursor-α (sAPPα), derived from the cleavage of amyloid protein precursor, notably enhances NMDA receptor function exclusively in aged animals, restoring impaired long-term potentiation (LTP) associated with aging. Yet, this effect is significantly reduced in SR knockout mice [ 47 ]. Overall, the results suggest that D-serine is crucial for the activation of NMDA receptors and NMDA receptor-mediated synaptic plasticity.…”
Section: Introductionmentioning
confidence: 99%